INDICES OF FREE RADICAL PROCESSES AND ANTIOXIDANT SYSTEM IN TUMOR TISSUE AND PERIFOCAL ZONE IN DIFFERENT CLINICAL VARIANTS OF BREAST CANCER - Ye. M. Frantziyantz; N. V. Soldatkina; L. A. Orlovskaya; A. V. Dashkov (ABV-press, 2014)
The aim of the study is to investigate the activity of free radical processes in tumor tissue and perifocal zone according to the dif- ferent clinical variants of breast cance: synchronous, metachronous and solitary. It is established, that in all clinical types of breast cancer the free radical processes in tumor tissue are repressed, activity of superoxide dismutase in the perifocal tissue is increased, the level of vitamins A and E is decreased and the level of common sulfhydric groups is increased. The ratio of the activ- ity of catalase in tumor tissue to the activity of this enzyme in the perifocal zone is 1,0±0,2 for metachronous breast cancer and 0,5±0,04 - for solitary variant of the disease. Given the ratio of the activity of catalase in tumor tissue of solitary variant of breast cancer to the activity of this enzyme in the perifocal zone of 1,0±0,2, it is possible to predict the possibility of metachronous breast cancer development.